Application of Value Analysis Methodology on a Wi-Fi Based Energy Monitor: A Case Study - Utkarsh Tiwari; Omprakash P.; V.S. Giri (Britain International of Exact Sciences (BIoEx) Journal, 2020)
An Energy Monitor is a device used for measuring energy and displaying the energy consumption. It is widely used in industrial and large commercial settings where high power is consumed. It has been observed that energy consumption can be reduced if monitored regularly and right actions are taken based on observations. There exists a need to integrate cloud technology with conventional technology in electronics product space, thus a Wi-Fi based Energy Monitor helps to achieve new heights in energy conservation. This technical paper aims to optimize cost and weight of a Wi-Fi based energy monitor to drive profitability, improve the reliability and increase the Value proposition of the product by the application of Value Analysis Methodology. A cross-functional Value Engineering team was formed to perform a case study on the Wi-Fi based Energy Monitor to identify the potential areas for optimization through Functional Analysis and Decision Matrix. The application of VAVE tools resulted in higher savings, decreased fault rate and reduction in weight of the product which led to a decrease in freight charges for the organization and increased the overall Value to the customers.